(Invited)650 Volt GaN Commercialization Reaches Automotive Standards. (17th August 2017) - Parikh, Primit; Smith, Kurt; Barr, Ron; Shono, Ken; McKay, J.; Shen, Likun; Lal, R.; Chowdhury, S.; Yea, S.; Smith, R. P.; Hosoda, T.; Gritters, J.; et al.
Abstract : With its proven ability to reduce size (form factor) and save energy (high efficiency) Gallium Nitride (GaN) is now no longer a nice to have, it is a must-have for power conversion. High voltage (HV) GaN HEMTs (also called GaN FETs) in the range of 650 to 900 volts are becoming the next standard for power conversion. GaN provides cost-competitive, easy-to-embed solutions that reduce energy loss by >50 percent, shrink system sizes by >40 percent, to simplify power converter/inverter design and manufacturing. These benefits are being realized today in various markets: Consumer, Industrial, Server, Servo Motors and Drives, Solar, Telecommunications, and recently Hybrid and Electric Vehicles. Having successfully completed JEDEC qualification and commercialization of HV-GaN, we will now review the first ever Automotive (AEC Q101) Qualification for GaN and discuss in detail results for highly stressed robustness tests, FIT rates & lifetime testing.